2021
DOI: 10.1111/jam.15086
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic diversity contributes more to sediment magnetism than abundance during incubation of iron‐reducing sediment from a non‐active volcanic lake in Northeast China

Abstract: Aim This study aimed to analyse bacterial community and biomineralization products from Wudalianchi non‐active volcanic field and the relationship between magnetization and bacterial community. Methods and Results Eighteen sediment samples obtained from Wenbo Lake, high‐throughput sequencing and quantitative PCR (qPCR) were separately employed to investigate the bacterial community composition dynamics and abundance variation of the sediment sample with the highest iron‐reducing capacity during incubation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…The substances after 0 and 120 h were collected and mineralogically characterized using SEM. Under NaCl-free conditions at 30°C, it was observed that the substance presented smooth surfaces with small conglomerates at the starting of experiment ( Figure 4A ), which is the Fe(OH) 3 ( Carrasco et al, 2021 ; Zhan et al, 2021 ). A large number of lenticular shape and plate-like structure, similar to Fe 3 (PO 4 ) 2 , were observed at 120 h ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 97%
“…The substances after 0 and 120 h were collected and mineralogically characterized using SEM. Under NaCl-free conditions at 30°C, it was observed that the substance presented smooth surfaces with small conglomerates at the starting of experiment ( Figure 4A ), which is the Fe(OH) 3 ( Carrasco et al, 2021 ; Zhan et al, 2021 ). A large number of lenticular shape and plate-like structure, similar to Fe 3 (PO 4 ) 2 , were observed at 120 h ( Figure 4B ).…”
Section: Resultsmentioning
confidence: 97%